Application of the academic evaluation by oral defense in training of nurses in the operating room (答辩式考核在手术室进修护士培训中的应用) - LI Wenjing (李文静); HU Juanjuan (胡娟娟); LIU Juan (刘娟); ZHAO Jing (赵晶) (Association of Integrative Nursing, 2021)
Objective To explore the application of academic evaluation by oral defense in training of nurses in the operating room. Methods A total of 36 nurses participating in the clinical training in the Department of Operating Room from January 2017 to June 2018 were selected as the control group, and 40 nurses from July 2018 to December 2019 were selected as the observation group. A personalized training program was developed for the nurses and standardized teaching method was carried out. The control group adopted routing evaluation in theory and practice skills, and the observation group implemented the academic evaluation by oral defense in addition to the routine evaluation. Results The theoretical and operational performance of nurses in the observation group were higher than those of nurses in the control group(P＜0. 01). The score of satisfaction assessment was (93. 00±5. 60)in the control group, which was lower than (98. 00±4. 40)in the observation group (P＜0. 01). Conclusion The application of academic evaluation by oral defense in the training of nurses is potentially effective to increase the satisfaction of the nurses, and is beneficial to the improvement of the theoretical knowledge level and practice skills. (目的 探讨答辩式考核在手术室进修护士培训中的应用效果。方法 选取科室2017年 1月-2018年6月进修护士36 名为对照组, 2018年7月-2019年12月进修护士40名为观察组。针对手术室进修护士制定个性化培训方案, 进行规范化教学, 对照组采用传统理论、操作考核, 观察组实施答辩联合理论、操作考核方式。检验进修护士的培训效果。结果 观察组理论成绩和操作成绩均高于对照组, 差异有统计学意义(P＜0. 01)。满意度评价结果显示, 对照组评分(93. 00±5. 60)分, 低于观察组评分(98. 00±4. 40)分, 差异有统计学意义(P＜0. 01)。结论 将答辩式考核用于手术室进修护士的培训中, 有利于增加进修护士的满意度, 提高进修护士理论和操作水平。)